ANALISIS VALIDITAS AKAD IJARAH DALAM PEMBIAYAAN MULTIJASA DI PERBANKAN SYARIAH: AKAD IJARAH, MULTIJASA DAN PERBANKAN SYARIAH - Romlah; Kusyana, Kusyana (Tasyri' : Jurnal Muamalah dan Ekonomi Syariah, 2022)
This paper presents an analysis of the validity of Ijarah contracts in multi-service financing within Islamic banking. Ijarah, as a prominent Islamic finance mechanism, serves as a crucial tool in providing financial solutions adhering to Sharia principles. The study examines the applicability and compliance of Ijarah contracts in various multi-service financing scenarios, highlighting their effectiveness in maintaining ethical standards and financial stability.The research identifies several challenges that affect the sustainability and adherence to Sharia principles in Ijarah contracts, including regulatory changes, market fluctuations, and customer awareness of Sharia-compliant products. These challenges necessitate strategic measures to ensure the continued validity and ethical soundness of Ijarah practices in Islamic banking. Recommendations are proposed to enhance the implementation of Ijarah contracts, including increased customer education, flexibility in contract structuring, rigorous internal oversight, collaboration with regulatory authorities, and continuous innovation in product development. These measures aim to strengthen the integrity and viability of Ijarah contracts in multi-service financing, contributing to the sustainable growth of Islamic banking while upholding Sharia principles. Keywords: Ijarah, Multi-service financing, Islamic banking, Validity, Sharia principles